Lumière du logos sur une conscience obscure - Clerget, Joël (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2022)
The recent reissue of the Bachelard’s book Le matérialisme rationnel (Paris, Puf, 2021) provides the opportunity to compare the work of Jacques Lacan with that of Gaston Bachelard. The philosopher’s contribution enlightens the clinic through the reflections it inspires in the practitioner. The concept of the unconscious, as well as the value of psychoanalysis, do not have the same heuristic and epistemological significance in both, but are established, for both, on a praxis of speech. Two axes guide this path. One takes into account a proposal from Bachelard: “to incorporate the conditions of application of a concept in the meaning of the concept”. The other takes up an evocation of Lacan: what psychoanalysis teaches us, how to teach it? Thus, psychoanalysis is considered in its participation in science and in transmission in the dimension of transference and desire.